If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x-2)/4=2x+8
We move all terms to the left:
(3x-2)/4-(2x+8)=0
We get rid of parentheses
(3x-2)/4-2x-8=0
We multiply all the terms by the denominator
(3x-2)-2x*4-8*4=0
We add all the numbers together, and all the variables
(3x-2)-2x*4-32=0
Wy multiply elements
(3x-2)-8x-32=0
We get rid of parentheses
3x-8x-2-32=0
We add all the numbers together, and all the variables
-5x-34=0
We move all terms containing x to the left, all other terms to the right
-5x=34
x=34/-5
x=-6+4/5
| x/2+0.5=-0.5 | | 38-2n=n+5 | | 4x^2-42x=0 | | 173=229-w | | 11x-2x+68=11x+38 | | -w+229=17 | | (2x+1)(x+9)=(2x+1)(x+9) | | √5x+4=17 | | 7+16t-4.905t^2=0 | | 71-x=291 | | 3x-7=3(3x-9)+2 | | T=(2x+85) | | (2y-15)+y+20=180 | | 10^{3x}-5=314 | | (y+4)/10=0 | | 3x+20=2x+20 | | 2y/19=4 | | 5x-0=9 | | 75,000=10,000(1.09)3x | | −(2−10c)=43+5c | | (y+9)/2=3 | | 6x-40=90° | | 3^x=181 | | 13.6(–3v+1)=5(–2v–2) | | 1/4(-12c+20)=-5-c | | y/3+0.5=0 | | 34x−5=4x= | | 3m-2=5m+42 | | 34x−5=4 | | (3x+1)^2+5(3x+1)-6=0 | | 6y-15=35+2y | | 8/z-8+1=z/z+8 |